Chemical engineering - Backhurst, J.R (Buuerworth; Heinemann, 2001)
Solutions to the problems in chemical engineering Volume 1; 13 parts: Inits and dimensions; flow of fluids - energy and momentum relationships; flow in pipes and channel; flow of compressible fluids; flow of multiphase mixtures;...